Retraction of Complaints Among Female Victims of Intimate Partner Violence Living in Poverty in Nicaragua - Rodríguez Vázquez, José Juan (International journal of offender therapy and comparative criminology, 2018)
Retraction among female victims of intimate partner violence (IPV) who report their abuser is a major problem in all societies. This article describes a study of 136 female victims of physical IPV living in poverty in Nicaragua, one of the countries with the lowest levels of development in Central America. This article analyses the aspects that differentiate women living in poverty who retracted after reporting IPV from those who did not. The results show that retraction is widespread among female victims of IPV living in poverty in León (Nicaragua). Although it is difficult to predict the retraction behaviour of the respondents, some differences between the women who retracted their complaint and those who did not were observed. A combination of five variables (including personal circumstances and beliefs about the intimate partner relationship and family) was the best alternative for discriminating between women who had retracted and those who had not.